All hail the queen - David, Erica (David, Erica. Anna & Elsa, 2015)
Adventurous Anna and snow magic-wielding Elsa explore the mountains, fjords and palace of their kingdom while getting to know each other as sisters. Now that the castle gates are open, Anna and Elsa are thrilled to be finally getting to know their kingdom. Anna bubbles with enthusiasm for all the things to do and the people to meet in Arendelle, and Elsa loves using her magic to help the town. But ruling a kingdom can be tiring-- and more than anything, the sisters want to spend time together!